Phonological contribution during visual word recognition in child readers. An intermodal priming study in Grades 3 and 5. (24th February 2016) - Sauval, Karinne; Casalis, Séverine; Perre, Laetitia
Abstract : This study investigated the phonological contribution during visual word recognition in child readers as a function of general reading expertise (third and fifth grades) and specific word exposure (frequent and less‐frequent words). An intermodal priming in lexical decision task was performed. Auditory primes (identical and unrelated) were used in order to directly activate phonological codes independently of orthographic processing. Overall, the results revealed a widespread phonological priming effect in both grades. There was a significant interaction between grade, priming condition and frequency, revealing that the impact of frequency on identity priming differed between grades. In third grade, the results indicated that the priming effect was greater for less‐frequent than for frequent words. In fifth grade, priming effects were similar for both frequent and less‐frequent words. These findings indicate that print and speech processing systems are interconnected in young readers. Moreover, phonological codes play an important role in word recognition throughout reading development.